A rabbit model of corneal Ectasia generated by treatment with collagenase type II - Qiao, Jing (BMC Ophthalmol, 2018)
BACKGROUND: To investigate use of collagenase type II for generating a rabbit model of corneal ectasia. METHODS: Ten New Zealand white rabbits were used with right eyes treated as the experimental group and left eyes treated as the control group. After epithelial debridement, a collagenase type II solution (200 μL of 5 mg/mL) was applied in the experimental group at room temperature (24 °C) for 30 min, and a 200 μL solution without collagenase was applied in the control group. Slit-lamp microscopy, the mean keratometry (Km), and central cornea thickness (CCT) were examined before and after the procedure. Corneas were obtained on day 14 for biomechanical evaluation. RESULTS: No obvious inflammatory reaction was observed in all eyes after the procedure. A statistically significant increase in Km (1.54 ± 1.29D vs − 0.82 ± 0.44D at day7 and 0.89 ± 0.89D vs − 2.11 ± 1.02D at day14) and a statistically significant decrease in CCT (− 23.10 ± 12.17 μm vs 6.20 ± 16.51 μm at day7 and − 16.10 ± 10.46 μm vs 11.60 ± 0.88 μm at day14) were observed in the experimental group compared with the control group. The mean stresses and elastic modulus at 5%, 10%, 15%, and 20% deformities in the experimental group decreased and the differences in elastic modulus between the two groups were statistically significant at 10% and 15% deformities. CONCLUSIONS: Collagenase type II treatment results in mimic KC with increased corneal keratometry and corneal thinning and a lower elastic modulus. An animal model for corneal ectasia can be generated by treatment with collagenase type II.